Fostering Reflective Practice: A Pathway to Effective Teaching and Professional Growth - Feruza Masharipova (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
This article explores the significance of reflective practice in English language teaching, emphasizing its role in fostering professional development and improving instructional effectiveness. The study discusses various models of reflection, particularly Gibbs’ Reflective Cycle, to analyze how teachers can critically assess and enhance their teaching strategies. By integrating reflection into lesson planning and classroom activities, educators can develop deeper insights into their pedagogical approaches. The article also highlights the importance of reflection in pre-service teacher education programs, particularly within the AELLCA project initiative by British Council in Uzbekistan and Central Asia. Drawing on theoretical frameworks from Schön, Gibbs, and Edwards, the study provides practical recommendations for implementing reflection in pre-service and continuing in- service system. Findings suggest that structured reflection enhances teachers’ ability to adapt, innovate, and respond to diverse classroom challenges. Additionally, reflective practice contributes to fostering learner autonomy and improving student engagement. The article concludes with a discussion on the long-term impact of reflective teaching on career sustainability and educational quality.